Improvement of Traditional Protection System in the Existing Hybrid Microgrid with Advanced Intelligent Method - Khandare, Pooja; Deokar, Sanjay; Dixit, Aarti (International Journal of Data Science, 2020)
The sustainable power sources will turn out to be a long haul future arrangement over conventional existing accessible source. Numerous specialized difficulties are ascending in the developing system of the Indian Microgrid; protection is one of it. Traditional protection framework utilized directional overcurrent transfers for the assurance against different deficiencies. These are dependent on the presupposition of the unidirectional progression of Current. The similar strategy cannot matter to the microgrid security as a bidirectional progression of current streams because of the nearness of DGs, which prompts specialized difficulties in the Microgrid. The new advanced intelligent method of DWT-differential Algorithm proposed over traditional protection system. The various parameters such as PS (Plug setting), TS (time setting), CDS(current duration setting) and operating time of relay tested. Indian Microgrid concentrated as contextual analysis, and smart system of microgrid protection prescribed to defeat all challenges got from writing contemplated. The system is designed in MATLAB software ,Double line to ground fault is simulated at different locations and DWT-DA is applied.The percentage of reduction obtained in operating time and other parameters are results in increasing reliability of microgrid.